BUKU LAGU DIGITAL ANAK INDONESIA CERIA UNTUK TAMANKANAK-KANAK:STUDI PENGEMBANGAN MEDIA AUDIOVISUAL - Alrizka Hairi Dilfa; Esy Maestro; Irdhan Epria Dharma Putra (SENDRATASIK UNP, 2018)
Abstract The purpose of this research was to find out the feasibility of an audiovisual media development product of Digital Books of Cheerful Indonesian Kids for Kindergarten. The type of research was R & D (Research and Development).The product was developed through five stages of modified work procedure from Borg and Gall product development procedure with stages: (1) planning, (2) Initial Product Development, (3) Validation of product, (4) Trial, and (5) Final Product. The data collection instrument was a questionnaire. Data were analyzed in the form of descriptive quantitative in order to know the product quality. In this research development, there wasfour persons of materials validator which consisted of two media validator.Based on the validation assessment of material validator and media validator, the result of the material validity was 85.7% and the results of the assessment of the media validator got the value of 80% and the average validation value was 82.85%. It means the product is in the valid category. It can be concluded that the product developed feasible to be tested. For the practicality, this media was categorized practical through the practicality test with an average practice score of 86.66%. It can be concluded that a digital booksongis worthy media and able to be used in the singing process in Kindergarten.Keyword: Development Study, Borg and Gall, Digital Book Song, Audiovisual Media.